2021
DOI: 10.1371/journal.pone.0251811
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal fistula after definitive concurrent chemotherapy and intensity modulated radiotherapy for esophageal squamous cell carcinoma

Abstract: Background The literature regarding esophageal fistula after definitive concurrent chemotherapy and intensity modulated radiotherapy (IMRT) for esophageal squamous cell carcinoma (ESCC) remains lacking. We aimed to investigate the risk factors of esophageal fistula among ESCC patients undergoing definitive concurrent chemoradiotherapy (CCRT) via IMRT technique. Methods A total of 129 consecutive ESCC patients receiving definitive CCRT with IMRT between 2008 and 2018 were reviewed. The cumulative incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
2
26
2
Order By: Relevance
“…There was no significant correlation between the development of EF and tumor with ulceration or esophageal stenosis in the regression equation. This result is inconsistent with those of other studies ( 7 9 , 12 14 , 16 ). This finding may be due to the different assessment methods used in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…There was no significant correlation between the development of EF and tumor with ulceration or esophageal stenosis in the regression equation. This result is inconsistent with those of other studies ( 7 9 , 12 14 , 16 ). This finding may be due to the different assessment methods used in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, reports on the effects of diabetes on EF are rare. Some studies tracking risk factors in EF did not show an effect of diabetes status ( 7 , 9 ), while our study found that diabetes increases the risk of RT-related EF by more than seven times in ESCC.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Previous literature ( 6 , 8 , 12 ) described that several clinical parameters are closely correlated with the occurrence of EF, including age, T stage, N stage, stenosis, ulceration, low serum cholesterol level, and body mass index (BMI). However, a unified diagnosis criterion for esophageal stenosis has not been unified, and the majority of studies defined stenosis solely based on symptoms ( 4 , 8 , 13 ).…”
Section: Introductionmentioning
confidence: 99%